Risk Analysis of Cayenne Pepper (Capcisum frutescens L.) Farming in Wantulasi Village, Wakorumba District, North Buton Regency - Aspiah Endrika Sari; Fahria Nadiryati Sadimantara; Yusna Indarsyih (International journal of technology and education research, 2025)
The study aims to know the risks that will be faced by ceyenne pepper farmers in Wantulasi Village, Wakorumba District, North Buton Regency. Respondent ceyenne pepper farmers were 38 people, identification of samples which was done using the census method (saturation sampling). The data retrieval using the questionnaire and the data analysis used is the coefficient analysis of variations. The results showed that the cultivation process of ceyenne pepper has a risk in its stage that is ranging from land processing, seed preparation, planting, fertilization, pest and disease and harvesting. While the risks of production of a coefficient variation (CV) of 0.013, the risks of price of a coefficient variation (CV) of 0.002 and then income risks from a coefficient variation (CV) of 0.012. It means that if the value of CV> 0.5 then the risk that the farmer is taking increases, whereas CV ≤ 0.5 then the risk that the farmer is taking is smaller. The average income from the ceyenne pepper farmers in one year was Rp 8,787,684